Yield related traits for the selection of early hybrids in subtropical maize. - Preciado, Ernesto (2016)
With the aim of designing selection criteria to identify the described genotypes with short vegetative period and longer grain-filling period without increasing the total growing cycle of the genotype. The information generated during 1995 at six locations in the subtropical region of Mexico was used. A serie of six experiments, integrated with a group of subtropical hybrids derived from a diallel between a group of elite tropical and subtropical inbred lines from CIMMYT, were evaluated in collaboration with INIFAP and the seed industry. In the combined analysis of six environments, early hybrids with a grain yield of 8.0 t/ha were identified; those hybrids were 14 days earlier to reach physiological maturity than the control check which yielded 7.4 t/ha. The genotypes with lower yields showed a short grain filling period compared to the vegetative period. Correlations among yield vs. days to physiological maturity, grain-filling period and the index calculated by dividing the between grain-filling /days to physiological maturity were 0.47, 0.53 and 0.41, respectively. This indicate an intermediate association between these traits; also, a high correlation values were observed between grain yield vs. plant and ear hight. The correlation between yield vs. days to silk and days to pollen shed were not significant. General combining ability (GCA) and specific combining ability (SCA) effects were significant for yield, days to silk and grain-filling period. Sufficient variation was observed to allow for the selection of genotypes with short vegetative periods and longer grain filling periods. The effects of GCA and SCA for grain-filling period suggest that this trait is an important criterion to select parents for producing short season hybrids.